Change your brain, change your body : use your brain to get and keep the body you have always wanted - Amen, Daniel G. (Harmony Books, 2010)
The author of "Change Your Brain, Change Your Life" and "Magnificent Mind at Any Age" explains how to harness brain power to improve overall health and body function.